Batik Tulis Lasem: Perlindungan Berbasis Inventarisasi Kekayaan Intelektual Komunal - Made Aditya Pramana Putra (Fakultas Hukum, Universitas Warmadewa, 2024)
This article aims to analyze the legal protection of Batik Tulis Lasem from the perspective of communal intellectual property. This research also aims to examine steps that can be taken by the government as an effort to protect Batik Tulis Lasem. This paper uses normative legal research methods with a statutory approach, a conceptual approach and an analytical approach. The results of the study show that the existence of Batik Tulis Lasem, which continues to be passed down from generation to generation from generation to generation, with the meaning and values contained in each element, deserves to be protected by the state as Communal IP in the form of TK and TCE. Steps that can be taken by the Government as an effort to protect Batik Tulis Lasem is to carry out an inventory as one of the Communal IPs that continues to be passed down from generation to generation from generation to generation with the meaning and value contained in each element. The inventory is carried out through 1) recordation and 2) data integration. Based on Permenkumham 13/2017, it is known that the inventory process is important to carry out as a defensive mechanism. Therefore, collaboration between all stakeholders plays a major role in collecting all data related to the existence and description of KIK itself.